CHALLENGES AND PROSPECTS FOR THE CHAGOS ARCHIPELAGO - Jeffery, Laura; Monaghan, Christopher; O'Gorman, Mairi (Abingdon, Oxon ; New York : Routledge, 2025)
"Challenges and Prospects for the Chagos Archipelago considers the origins, challenges and future of Chagos, bringing together leading experts and academics specialising in differing aspects of the Chagos dispute. In November 1965 the United Kingdom created the British Indian Ocean Territory out of the Chagos Islands, which it had 'encouraged' Mauritius, then a British colony, to give up in return for a promise of independence. The UK then set about removing the population of the Chagos Islands in order to allow the United States to construct a military base. As a consequence of the UK's acquisition of the Chagos Islands and the expulsion of the Chagossian population, there has been wide ranging litigation brought by Mauritius and the Chagossians. This has reached the International Court of Justice, the United Nations General Assembly, the European Court of Human Rights and the UK Supreme Court. This book offers a wide-ranging debate between experts and practitioners, including those of Chagossian and Mauritian heritage, touching upon key developments and offering an inclusive approach that transcends traditional disciplinary silos. Issues such as international and constitutional law, human rights, colonialism and decolonisation, using creative writing to express the experience of banishment, international relations, environmentalism, and globalisation, will be explored as part of a dialogue that sheds new light on the Chagos dispute. Edited by experts on Chagos, the contributors are drawn from across the globe, and all have a distinctive take on what has happened, what it means for the world and the region, and how Chagos will both shape and be shaped by the future. This book will be of great interest to students, academics and researchers from across the humanities and social sciences, including political science, international relations, law, sociology, socio-legal studies, human rights, social anthropology, indigenous rights, history, colonialism, postcolonialism, and cultural studies, as well as practitioners, policymakers and general readers who are interested in Chagos"--
The Chagos saga: 21st century dispute about incomplete decolonisation / Milan Meetarbhan -- The Chagos Archipelago in late eighteenth- and nineteenth-century Indian Ocean world history / Richard Allen -- Origins, legacies, and future: the Chagossians, a population in exile / Priya Bahadoor -- So immaculate -- Peros Banhos, Saloman, Diego Garcia / Saradha Soobrayen -- Chagos: plantation or paradise? Island Edens and Indian Ocean empires, 1600-2023 / Chris Hill -- Human rights and the Marine Protected Area around the Chagos Archipelago / Sue Farran -- Return of the Chagos Islands to Mauritius and Chagossian identity: constitutional, legal, and political perspectives / Charles Fombad -- Political and legal debates about Chagossian ethnicity and indigeneity / Laura Jeffery -- Intergenerational challenges, cultural identify, and future prospects for Chagossian communities in the UK / Thierry Mandarin -- Ayapana in a British plastic plant pot / Chrisyl Wong-Hang-Sun -- Certainty and uncertainty: native and older generation Chagossian perspectives from Mauritius amid the UK Government's Nationality and Borders Act 2022 / Chrisyl Wong-Hang-Sun -- Limuria is in our trust / Chrisyl Wong-Hang-Sun -- Voicing the trauma of the lost territory: creative writing, therapy and the Chagos Refugees Group / Esther Pujolràs-Noguer and Felicity Hand -- This poem is intuitively aware of the erasure of the Chagos Archipelago... / Saradha Soobrayen -- Excerpt from Diego Garcia, a novel / Natasha Soobramanien and Luke Williams -- The British courts and the Chagos story: an exercise in colonial justice / Satvinder Juss and Chris Monaghan -- Stakeholders or bystanders? An attempt by Seychellois Chagossians to intervene in the International Tribunal for the Law of the Sea / Jamie Trinidad, Stephen Allen and Thomas Burri -- The 1966 BIOT Agreement and Polaris / Samuel Bashfield -- The power behind the throne: the US Government must face its responsibility for the Chagossian exile / David Vine -- 'UK Ambassador lobbied senators to hide Diego Garcia's role in rendition' / Saradha Soobrayen -- The Indo-Pacific and the Chagos Archipelago: two logic's, two futures / Peter Harris -- Flagpole fights, courtroom clashes, and coconut crabs / Owen Bowcott -- Why has it taken 25 years for the UK to start negotiating an overall settlement on Chagos with Mauritius? / David Snoxell -- An ode to the Chagossian zistwar / Chrisyl Wong-Hang-Sun -- Afterword / Sabrina Jean.
Keywords: British Indian Ocean Territory -- International status; British Indian Ocean Territory -- Politics and government; Chagossians -- Legal status, laws, etc. -- Social aspects; Chagossians -- Political activity; Chagossians -- Ethnic identity; Population transfers -- Chagossians; Forced migration -- British Indian Ocean Territory; Refugees -- British Indian Ocean Territory; Human rights -- British Indian Ocean Territory; British Indian Ocean Territory -- History